SYNTHESIS, CHARACTERIZATIONAND APPLICATION OF DIATOMACEOUS EARTH - 4,4- DIAMINODIPHENYLETHER-O-HYDROXYBENZALDEHYDEAS AN ADSORBENT OF Ag(l) METAL ION - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
ABSTRACT Synthesis, characterization and application of Diatomaceous Earth-4,4-Diamino diphenylether-OHydroxybenzaldehyde(diatomaceousearth-DDE-O-Hb)as an adsorbent of Ag(l) metal ion has been done. The aim of the purification of natural diatomaceous earth with KMn04, H~04 and HCI were to obtain pure diatomaceous earth, remove the other compoundsand de-alumination,respectively. The adsorbentof diatomaceousearth-DDE-OHb was synthesized by reacting pure diatomaceous earth with 3-chloropropyltrimethoxysilane, 4,4- diaminodiphenylether (DDE) and O-hydroxybenzaldehyde (O-Hb). The FTIR spectroscopy was used to identify Schiff base group in diatomaceousearth-DDE-O-Hbadsorbent. The diatomaceousearth-DDE-O-Hbwas applied as adsorbent in the adsorption of Ag(l) metal ion. Parameters influencing the interaction such as time, pH and concentration were optimized. The result showed that diatomaceous earth-DDE-O-Hb adsorbent have Schiff base group. The interaction time of 90 min showed that 70.79% of Ag(l) metal ions at the concentration of 100ppm can be adsorbed by diatomaceous earth-DDE-O-Hb adsorbent. At the pH solution between 2 to 7, the concentration of 100ppm of Ag(l) metal ion that can adsorbed by diatomaceous earth-DDE-O-Hb adsorbent was up to 98% and at the concentration of 25 ppm Ag(I) metal ion, the adsorption of Ag(l) by diatomaceous earth-DDE-O-Hb adsorbent was near 91%.